Distributed scheduling of sensor networks for identification of spatio-temporal processes - Patan, Maciej (1975- ) (Zielona Góra: Uniwersytet Zielonogórski)
An approach to determine a scheduling policy for a sensor network monitoring some spatial domain in order to identify unknown parameters of a distributed system is discussed. Given a finite number of possible sites at which sensors are located, the activation schedule for scanning sensors is provided so as to maximize a criterion defined on the Fisher information matrix associated with the estimated parameter
Keywords: distributed-parameter system; parameter estimation; running consensus; scanning measurements; sensor network